(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
As the medical data keeps growing day by day, it is difficult to search for relevant information from the huge data. Improper medications may lead to serious health risks and even may result in the death of the patient. The recommender systems can be used to provide suggestions based on the health status. This approach aims to develop an efficient recommendation system which is responsible for recommending medicines for the disease based on the symptoms. This system would help the doctors in prescribing medications correctly without medication errors.